2011
DOI: 10.1111/j.1365-2427.2011.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and the effects of elemental food quality on Daphnia

Abstract: 1. We examined the responses of two species of Daphnia to changes in food phosphorus (P) content, with animals reared at three different water temperatures. Specifically, we measured mass-specific growth rate (MSGR), body P content and respiration rate of Daphnia magna and Daphnia pulex acclimatised to 10, 17.5 and 25°C and fed food carbon : phosphorus (C : P) ratios of either 150 or 500. 2. The responses of these three physiological variables to temperature-food quality interactions were species-specific. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 30 publications
4
53
0
Order By: Relevance
“…Persson et al [33] found no evidence of Daphnia P limitation at the lowest temperature (108C), indicating that enzyme kinetics or other measures of food quality were more important for somatic Daphnia growth than the demands for P to RNA and protein. By contrast, McFeeters & Frost [43] demonstrated that the effects of high C : P on the growth of Daphnia magna decreased with temperature and noted that contrasting results may suggest that at low temperatures thermal constraints can reduce or mask the effects of poor food quality. All these findings and the results of our study imply that in order to assess stoichiometric food quality effects on natural zooplankton populations, the in situ temperature needs to be taken into account.…”
Section: (I) Population Grazing Ratesmentioning
confidence: 99%
“…Persson et al [33] found no evidence of Daphnia P limitation at the lowest temperature (108C), indicating that enzyme kinetics or other measures of food quality were more important for somatic Daphnia growth than the demands for P to RNA and protein. By contrast, McFeeters & Frost [43] demonstrated that the effects of high C : P on the growth of Daphnia magna decreased with temperature and noted that contrasting results may suggest that at low temperatures thermal constraints can reduce or mask the effects of poor food quality. All these findings and the results of our study imply that in order to assess stoichiometric food quality effects on natural zooplankton populations, the in situ temperature needs to be taken into account.…”
Section: (I) Population Grazing Ratesmentioning
confidence: 99%
“…Considerable evidence exists for clonal-and species-specific responses in daphniids (Jiang et al forthcoming 2013). For example, the responses of physiological variables to temperature-food quality interactions reported by McFeeters and Frost (2011) were restricted to one of the two Daphnia species studied. Further studies are needed to investigate whether the effects of ecological variables in temperature reaction norms are clonal and/or species specific.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, during cold months, the availability of high-quality resources may not be as critical, because temperature likely limits the growth rates of consumers and ingested resources are largely dedicated to fueling basal metabolism instead of new tissue growth. Others, however, have shown that food quality effects on growth may be greater at cold temperatures and can vary across species (McFeeters and Frost 2011). Such an effect may be driven by constraints on physiological mechanisms for countering poor food quality at cold temperatures.…”
Section: Epilithic Algaementioning
confidence: 99%